Secured map reduce computing based on virtual machine using threshold secret sharing and group signature mechanisms in cloud computing environments - Lin, Hua Yi; Hsieh, Meng-Yen; Li, Kuan-Ching (Telecommunication systems, 2015)
Nowadays, cloud computing becomes a popular technology which combines resources of numerous physical computers and servers to perform distributed computing. The main benefit of cloud computing is that this technology decreases computing costs and infrastructures, allowing much more efficient computing. Through a portal, users submit working tasks and receive the results without assigning to specific servers. Nevertheless, the computers of users and enterprises are located in cloud, and arbitrary clients can randomly log on and take private data away. Thus, the cloud security becomes a significant subject. In this paper, we exploit the threshold crypto sharing (Desmedt and Frankel in Advances in cryptology—CRYPTO’89, 1990 ) with group signature mechanism to secure transmitted data. During map and reduce phases, this mechanism can protect the divided and merged messages from being tampered with. Additionally, this study exploits a virtual machine platform to simulate cloud computing environments and then perform security operations. Experimental results show that the mechanism presented has lower cost comparing to other existing ones and very promising its application in cloud environments.